The impact of digital art-making on anxiety: a feasibility study - Gallo, Laura M. H.; Giampietro, Vincent; Choi, Minu (Frontiers in Psychology, 2025)
Extensive research shows art-making reduces stress and activates the brain’s reward system, yet few studies explore remote digital art interventions. This feasibility study examines whether a remote digital art-making intervention can reduce anxiety. It offers preliminary insights into the potential of online art tools to broaden access to creative expression. Participants engaged in an eight-week program using the Mindful of Art platform, which enables digital art-making without technical skills. Each week, they completed a themed task designed to encourage creativity and reduce self-criticism, along with surveys measuring anxiety, flow, and affect. At registration, we collected demographic data, artistic interest, self-perceived creativity, and trait anxiety. Trait anxiety was reassessed after 8 weeks, regardless of participation level. Results suggest digital art-making can help reduce anxiety, especially in highly anxious individuals. Effects were independent of artistic interest or self-perceived creativity. This suggests self-guided digital art-making could be a scalable, affordable complement to existing mental health services. While intervention frequency did not predict outcomes, our findings align with prior research suggesting art based interventions support mental wellbeing, and highlight the potential of digital art-making as an accessible, low skill self-help tool for anxiety management.